Article Synthesis of Chitosan Beads Incorporating Graphene Oxide/Titanium Dioxide Nanoparticles for In Vivo Studies (2020)
Sca old development for cell regeneration has increased in recent years due to the high demand for more e cient and biocompatible materials. Nanomaterials have become a critical alternative for mechanical, thermal, and antimicrobial property reinforcement in several biopolymers. In this work, four di erent chitosan (CS) bead formulations crosslinked with glutaraldehyde (GLA), including titanium dioxide nanoparticles (TiO2), and graphene oxide (GO) nanosheets, were prepared with potential biomedical applications in mind. The characterization of by FTIR spectroscopy, X-ray photoelectron spectroscopy (XRD), thermogravimetric analysis (TGA), energy-dispersive spectroscopy (EDS) and scanning electron microscopy (SEM), demonstrated an e cient preparation of nanocomposites, with nanoparticles well-dispersed in the polymer matrix. In vivo, subdermal implantation of the beads inWistar rat0s tissue for 90 days showed a proper and complete healing process without any allergenic response to any of the formulations. Masson0s trichrome staining of the histological implanted tissues demonstrated the presence of a group of macrophage/histiocyte compatible cells, which indicates a high degree of biocompatibility of the beads. The materials were very stable under body conditions as the morphometry studies showed, but with low resorption percentages. These high stability beads could be used as biocompatible, resistant materials for long-term applications. The results presented in this study show the enormous potential of these chitosan nanocomposites in cell regeneration and biomedical applications.